Nutritional Intervention Strategies Using Dietary Antioxidants and Organic Trace Minerals to Reduce the Incidence of Wooden Breast and Other Carcass Quality Defects in Broiler Birds - Kuttappan, Vivek A.; Manangi, Megharaja; Bekker, Matthew; Chen, Juxing; Vazquez-Anon, Mercedes (Frontiers in Physiology, 2021)
Wooden breast (WB) is a degenerative myopathy seen in modern broiler birds resulting in quality downgrade of breast fillets. Affected fillets show increased toughness both before as well as after cooking and have decreased water holding capacity and marinade pick up compared to normal fillets. Although the exact etiology is unknown, the circulatory insufficiency and increased oxidative stress in the breast muscles of modern broiler birds could be resulting in damage and degeneration of muscle fibers leading to myopathies. Three independent studies were conducted to evaluate the effect of various dietary interventions on the incidence of WB when birds are exposed to oxidative stress associated with feeding oxidized fat and mild heat stress. Feed additives such as dietary antioxidant (Ethoxyquin, ETX), mineral methionine hydroxy analog chelate (MMHAC) of Zn, Cu, and Mn, and organic selenium (Org Se) were tested at recommended levels. Results from the oxidized fat studies showed that feeding ETX, and MMHAC were able to improve performance and reduce incidence of WB Score 3 induced by the oxidized fat diet. The magnitude of reduction of WB and muscle lipid peroxidation was greater when ETX and MMHAC were fed together. In birds exposed to mild heat stress, feeding MMHAC by itself reduced tissue damage by reducing incidence of tibial head lesions, skin scratches, breast blisters, in addition to reducing the incidence of WB. When MMHAC was combined with ETX and Org Se, further reduction in WB were observed. In summary, under different oxidative stress conditions, dietary intervention programs that contain ETX, MMHA-Zn, -Cu, and -Mn and Org Se can improve performance and increase carcass integrity, reducing problems, such as WB, either independently or with additive effect. This effect is most likely attained by simultaneously improving the exogenous and endogenous antioxidant status, reducing oxidative stress, and improving tissue healing process of the bird.